Economic challenges,values and religion in the Costa Rican 2018 elections - Pignataro, Adrián; Treminio, Ilka (Revista de Ciencia Política, 2019)
In 2018 Costa Rica faced unprecedented elections due to the radicalization of the party supply, the diminished role of the traditional parties, and the unexpected continuity in government of the incumbent party with the presidency of Carlos Alvarado. During the campaign, the focus shifted from economic to self-expression issues (sexual education, equal marriage, abortion). Together with sociodemographic variables and the evaluation of the incumbent government, religion had an important explanatory weight on vote choice, especially after the advisory opinion of the Inter-American Court that recognized the fundamental rights of LGBTI people during the campaign. We discuss the consequences for the current government and the future elections.